2020
DOI: 10.3390/su12155957
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Competitiveness in the Global Beer Trade

Abstract: Beer is a widely produced, consumed, and traded alcoholic drink all around the world. This paper investigates the factors influencing competitiveness in the global beer trade on the macroeconomic level. To reach this aim, descriptive analysis and panel regression together with stability tests were used on the global beer market from 1998 to 2017. Results showed high concentration both in global production and trade, while except for the most competitive beer-exporting countries, the level of comparative advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
3
16
0
2
Order By: Relevance
“…The presented results are in compliance with former studies [9,27,[30][31][32][37][38][39][40][41], which identified and described similar factors influencing the expansion of craft beer in different countries, however, there are differences because of the diverse history of the countries, levels of income, regional differences, a tradition of drinking beer and its substitutes. Thanks to the gained data we have identified some of the reasons that influence the expansion of craft beer in the Czech Republic as stated above.…”
Section: Discussionsupporting
confidence: 91%
“…The presented results are in compliance with former studies [9,27,[30][31][32][37][38][39][40][41], which identified and described similar factors influencing the expansion of craft beer in different countries, however, there are differences because of the diverse history of the countries, levels of income, regional differences, a tradition of drinking beer and its substitutes. Thanks to the gained data we have identified some of the reasons that influence the expansion of craft beer in the Czech Republic as stated above.…”
Section: Discussionsupporting
confidence: 91%
“…Survival chances of 97% at the start of the period fell to 0% by 2018, implying stiff competition in the tea trade of the selected countries. Similar results also found regarding the European ham trade (Török and Jámbor, 2016) and global beer trade (Török et al, 2020). However, standard deviations of the RSCA indices over the whole study period are quite high (0.609) for Bangladesh, suggesting variation from year to year, and they seem to remain relatively unstable over the entire period.…”
Section: Comparative Advantage Of Tea Exportsupporting
confidence: 82%
“…Results indicated that low value of RCA implying the comparative advantage of Indonesia still needs to be improved because of losing opportunities to be able to trade with other countries. Török et al (2020) revealed that the level of comparative advantage of beer has substantially changed over three decades due to per capita beer production and consumption, the number of beers with geographical indications, and European Union (EU) membership. Likewise, Török and Jámbor (2016) reported that quality of production area and EU accession affect the competitiveness for ham trade of Europe.…”
Section: Export Competitiveness Of Tea and Other Agricultural Productsmentioning
confidence: 99%
“…Between 2008 and 2017, Namibia had the best comparative advantages in beer trade, followed by Jamaica, Mexico, Kenya, Serbia, Portugal and the Netherlands. The biggest beer exporters (Mexico and Netherlands in particular) also had comparative advantages [1,2]. In 2018, the Czech Republic, Austria, Germany, Romania and Poland had the highest per capita beer consumption rate globally [3].…”
Section: Introduction 1introductionmentioning
confidence: 99%